Effect of porosity and eutectics on the high-temperature low-cycle fatigue performance of a nickel-base single-crystal superalloy. (October 2018) - Ruttert, Benjamin; Meid, Carla; Mujica Roncery, Lais; Lopez-Galilea, Inmaculada; Bartsch, Marion; Theisen, Werner
Abstract: This work investigates the separate influence of porosity and γ/γ′-eutectics on the low-cycle fatigue life of a single-crystal Ni-base superalloy at high temperatures. A conventional vacuum furnace heat-treatment but also integrated heat-treatments in a hot isostatic press are applied to produce different material variants of the same alloy. High-resolution electron microscopy revealed that both pores and γ/γ′-eutectics act as crack starters, thus initiating early failure. Moreover, the results indicate that remaining γ/γ′-eutectics can weaken the fatigue resistance even more than pores. Furthermore, the results confirm the beneficial effect of proper integrated hot isostatic pressing heat-treatments on the fatigue performance. Graphical abstract: Unlabelled Image